Epigenetic differences in human cartilage between mild and severe OA. Issue 12 (12th September 2014) - Moazedi‐Fuerst, Florentine C.; Hofner, Manuela; Gruber, Gerald; Weinhaeusel, Andreas; Stradner, Martin H.; Angerer, Hannes; Peischler, Daniela; Lohberger, Birgit; Glehr, Mathias; Leithner, Andreas; Sonntagbauer, Markus; Graninger, Winfried B.
ABSTRACT The development of osteoarthritis (OA) depends on genetic and environmental factors, which influence the biology of the chondrocyte via epigenetic regulation. Changes within the epigenome might lead the way to discovery of new pathogenetic pathways. We performed a genome‐wide methylation screening to identify potential differences between paired mild and severe osteoarthritic human cartilage. Sixteen female patients suffering from OA underwent total knee joint replacement. Cartilage specimens collected from corresponding macroscopically undamaged and from damaged areas were processed for DNA extraction and histology to evaluate the histological grading of the disease. Paired specimens were analysed for the methylation status of the whole genome using human promoter microarrays (Agilent, Santa Clara, CA). Selected target genes were then validated via methylation‐specific qPCR. One thousand two hundred and fourteen genetic targets were identified differentially methylated between mild and severe OA. One thousand and seventy of these targets were found hypermethylated and 144 hypomethylated. The descriptive analysis of these genes by Gene Ontology (GO), KEGG pathway and protein domain analyses points to pathways of development and differentiation. We identified a list of genes which are differently methylated in mild and severe OA cartilage. Within the pathways of growth and development new therapeutic targets might arise by improving our understanding of pathogenetic mechanisms in OA. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1636–1645, 2014.